Increasing Physical Soil Quality by Using Rice Straw Biomass - Sumiyati Sumiyati; I Wayan Tika; Ni Nyoman Sulastri; Mentari Kinasih (The University of Lampung, 2024)
Paddy straw as an agricultural waste can be returned to the soil to increase the organic matter content. This study aims to determine the optimum inoculant treatment of rice paddy straw on soil quality. The straw handling was carried out by spreading the straw on paddy fields and sprayed with four inoculant treatments (0, 3, 6, 9, and 12 L/ha). The incubation process was carried out for 21 days and incorporated in the soil through plowing. Each treatment was repeated three times so that the total treatment was 15 units. The variables observed in each treatment were soil quality. The soil quality parameters observed were particle density, bulk density, porosity, field capacity and pH. ANOVA statistical analysis which was continued by the Tukey HSD Post Hoc Test to determine the effect of treatment on soil quality. The results showed that the inoculant treatments showed a significant difference (p-value=0.05) in soil volume, density, and porosity. P4 gave the optimum results which are statistically not significantly different from P3. P4 shows the physical properties of the soil which consist of the soil bulk density of 0.61 g/cm3; particle density 1.74 g/cm3; porosity was 64.91%, and pH 6.68. The utilization of straw biomass as source of organic material contributes to zero waste rice cultivation. Keywords: Effective microorganisms, Rice straw, Soil density, Soil pH, Soil porosity.